2020
DOI: 10.1016/j.heliyon.2019.e03119
|View full text |Cite
|
Sign up to set email alerts
|

Improved pyrolysis behavior of ammonium polyphosphate-melamine-expandable (APP-MEL-EG) intumescent fire retardant coating system using ceria and dolomite as additives for I-beam steel application

Abstract: This study describes the effects of ceria (CeO 2) and dolomite [CaMg(CO 3) 2 ] additives on the pyrolysis behavior and fire resistive property of conventional intumescent flame retardant (IFR) coating system for I-beam steel substrate called ammonium polyphosphate-melamine-expandable graphite (APP-MEL-EG) system. The fire resistance of various formulations was evaluated using the standard vertical Bunsen burner fire test. Thermogravimetric analysis (TGA) was used to understand the degradation of coating formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…As for the broad peak between 3000 and 3700 cm −1 , this is assigned to O–H vibrations of crystalline and/or free water molecules ( Tabelin et al., 2017c ; Zoleta et al., 2020 ). The presence of carbonate minerals is also implied by the broad IR absorption peak between 1600 and 1300 cm −1 in PA and MT.…”
Section: Resultsmentioning
confidence: 99%
“…As for the broad peak between 3000 and 3700 cm −1 , this is assigned to O–H vibrations of crystalline and/or free water molecules ( Tabelin et al., 2017c ; Zoleta et al., 2020 ). The presence of carbonate minerals is also implied by the broad IR absorption peak between 1600 and 1300 cm −1 in PA and MT.…”
Section: Resultsmentioning
confidence: 99%
“…The narrow scan spectra of oxygen (O 1s), carbon (C 1s), titanium (Ti 2p), and sulfur (S 2p) were obtained and corrected using the binding energy of adventitious carbon (285.0 EV). All XPS spectra were deconvoluted with XPSPEAK version 4.1 using a true Shirley background and a 20–80% Lorentzian–Gaussian peak model. , The specific surface area and pore size were analyzed using a BELSORP MAX X analysis instrument.…”
Section: Methodsmentioning
confidence: 99%
“…All XPS spectra were deconvoluted with XPSPEAK version 4.1 using a true Shirley background and a 20–80% Lorentzian–Gaussian peak model. 68 , 69 The specific surface area and pore size were analyzed using a BELSORP MAX X analysis instrument.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Zoleta et al. (2020) added ceria and dolomite to the fire‐retardant coatings of the ammonium polyphosphate‐MEL‐expandable graphite system and found that ceria not only catalyzes the release of water but also promotes the formation of P−O free radicals, thereby enhancing carbon strength [12] . Liu et al.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zoleta et al (2020) added ceria and dolomite to the fire-retardant coatings of the ammonium polyphosphate-MELexpandable graphite system and found that ceria not only catalyzes the release of water but also promotes the formation of PÀ O free radicals, thereby enhancing carbon strength. [12] Liu et al (2020) recycled powders with large amounts of flameretardant compositions from the precipitate of industrial effluents and applied them in an intumescent fire-retardant coating; such a high-performance intumescent flame-retardant coating is promising in the industry. [13] In the present study, the synergistic fire resistance of ceria and PEA on epoxy intumescent fire-retardant coatings was studied.…”
Section: Introductionmentioning
confidence: 99%